An Ethical Marketing and Compliance Framework for Pharmaceutical Representatives Engaging with Public Health Institutions - Michael Aduojo Amuta; Muridzo Muonde; Ashiata Yetunde Mustapha; Akachukwu Obianuju Mbata (International Journal of Scientific Research in Civil Engineering, 2022)
The intersection of pharmaceutical marketing and public health presents complex ethical challenges, particularly when pharmaceutical representatives engage directly with public health institutions. This paper proposes an ethical marketing and compliance framework tailored for pharmaceutical representatives operating in public sector contexts. Leveraging a mixed-methods approach, the study integrates qualitative insights from key informants in regulatory bodies and quantitative survey data from pharmaceutical professionals to construct a robust and actionable framework. The research emphasizes the need for transparency, regulatory adherence, and ethical conduct in pharmaceutical engagements to mitigate risks of undue influence, conflicts of interest, and regulatory violations. The findings underscore that institutional trust and long-term policy coherence depend on ethically grounded promotional practices and proactive compliance monitoring. The proposed framework offers a strategic guide for pharmaceutical firms, policymakers, and compliance officers aiming to institutionalize ethical standards in pharmaceutical marketing within the public health domain.